Tradisi Boke dalam Pesta Panen pada Masyarakat Kulisusu di Desa Lapandewa Kecamatan Kulisusu Barat Kabupaten Buton Utara - Jusman Jusman; Rahmat Sewa Suraya; La Ode Marhini (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2023)
This study aims to exmine the oral history of haroaano laa, the implementation process and the meanings of Bhoke in the boke tradition in the harvest festival in the community in Lapandewa Village, West Kulisusu District, North Buton Regency. The study used a qualitative descriptive method. The location of the study chosen was in Lapandewa Village, West Kulisusu District, North Buton Regency. Data collection techniques were carried out by direct observation, interviews with informants and documentation. Determination of informants using purposive techniques. Data were analyzed in four stages, namely; (1) data collection stage, (2) data reduction, (3) data presentation stage (4) conclusion drawing stage. The informants in the study numbered 5 people, Data collection in this study was carried out using observation, interview and documentation techniques which were then analyzed descriptively qualitatively. The results of this study are; (1) the harvest festival (haroano laa) is an annual tradition that has been carried out from ancient times to the present. The history of the harvest festival (haroano laa) when two people Labalubi and Labaura came to a place now called Lapandewa village. In this place there is a big river and is inhabited by many crocodiles, these two people also marked the place with a red flag and this flag is symbolized as a sign of danger. (2) The process of implementing Boke (a) Boke Preparation Stage (i) Determining a Good Day (ii) Time and place (iii) Tools and materials (iv) (b) Implementation stage (i) Pecking (Pompapecucu) (ii) Installing spurs (iii) Cockfighting (perumpa) (3). The meaning of Chicken in the Boke tradition in the Lapandewa Village community compares chickens to land that will be wagered where the chicken that wins the fight is considered land that has fertility and is free from disease outbreaks and disturbances from wild animals. The meaning of the Surabi and Bana spurs symbolizes harmony between communities.